Analisis Saluran dan Margin Pemasaran Bunga Potong Anthurium di Desa Candikuning, Kecamatan Baturiti, Kabupaten Tabanan - HASMURULLAH, FAQIH; USTRIYANA, I NYOMAN GEDE; ANGGRENI, I GAA LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2018)
This study aimed to determine the pattern of marketing channels, marketing margin of each marketing channel of anthurium cut flowers in the village of Candikuning and problems faced by anthurium cut flowers farmers in marketing their products. Basic method of this research was descriptive qualitative and quantitative. The research area was taken purposively, that is, Candikuning Village, Baturiti Dustrict, Tabanan Ragency. The method to determine the sample of respondents used census method for farmers, because out of the farmers of anthurium cut flowers in the Village of Candikuning there were eight farmers and snowvall sampling for marketing agencies. The data ware taken either in the form of primary data and secondary data through interviewing, recording and observation. The research result showed that there were two patterns of anthurium cut flower marketing channels in Candikuning Village i.e., channel I : Farmers ? Village Collectors ? Retailer Trades ? Consumers, channel II : Farmers ? Retailer Trades ? Consumers. The highest marketing margin was in the first pattern i.e. IDR 3.000 per stalk, for the pattern II amounted to IDR 2.500 per stalk. The higest share received by the farmers was in the marketing pattern II i.e. 37,5%. The problems faced by anthurium cut flower farmers in marketing their products were the price of anthurium flowers in yhe faremr level was low.